Water Privatization in Developing Countries: Case of Albania - Zeneli, Fjona (European Scientific Journal, ESJ, 2017)
A safe, clean, accessible and affordable drinking water and sanitation service for all individuals is a human right recognized explicitly from the United Nations General Assembly (Resolution 64/292, July 2010). Access to clean drinking water is so crucial for development that developed countries have made significant investments in water infrastructure (production, distribution investments in investments in piping, pumps, water purification systems and wastewater treatment plants etc.), managerial structures and capacities. The picture is very different in developing countries. One of the main problems is the lack of efficiency of the water systems, leading to a higher loss rate (from system leakage and illegal connections to the system) and cost-recovery failure because of the low revenues from tap water sales. In most of the cases governments fail to finance the financial loss of the water suppliers and in this way fail to fulfill the public need for drinking water and sanitation and water treatment services. So an alternative to solve the situation is seen the privatization of drinking water sector. The paper will give a summarized picture of the phenomenon in the world having as the case study the situation in Albania during years starting from the legislative frame, previous attempts to future tendencies related to the privatization of drinking water sector. The main objective is to explore the arguments pros and cons related to the privatization of â€œan economic goodâ€ such as water suggesting different alternatives in this context.